The Urgency of Blue Economy-Based Sustainable Development Education in Higher Education (Study Blue Economy Education in Probolinggo) - Siti Marwiyah; Nurul Jannah Lailatul Fitria (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This study aims to explain the urgency of blue economy education at the University of Probolinggo so that there are special materials related to the blue economy, both theory, practice, cooperation programs, and others to support the implementation of the blue economy. This research method uses a descriptive method with a qualitative approach. Informants are obtained from literature studies, namely research that uses various literatures, journals, books, research reports, and other references to answer and discuss topics. Other instruments in research use observation, interviews and documentation. The data analysis technique of this research is narrative analysis. The results of this study indicate that universities in Probolinggo as one of the educational institutions are currently faced with the challenge of how to prepare resources, namely equipping students with the ability to analyze, understand, and understand aspects of -multidimensional aspects of sustainable development issues, especially the blue economy program in Probolinggo. Educational reorientation can be considered as an effort to produce new generations of professionals in facing the transition period towards blue economy goals. So that it can be seen that it is important for universities to include blue economy education with various elements of knowledge, issues, skills, perspectives, and values that can be given to students at universities in Probolinggo.